Weed control methods effect on the hydraulic attributes of a Latosol - Pires, Luiz Fernando; Araujo-Junior, Cezar Francisco; Piccolomini Dias, Nivea Maria; Dias Junior, Moacir de Souza; Alcântara, Elifas Nunes de (Acta Scientiarum. Agronomy, 2017)
Weed management plays a key role in the minimization of soil physical degradation processes such as compaction and hydric erosion. Different weed control managements can induce distinct changes in soil structure. One important soil physical attribute used for the analysis of modifications in soil structure is the soil water retention curve (SWRC). The objective of this work was to verify the use of physico-hydrical attributes to understand the effect of weed control managements on soil structure. Two soil layers (0–0.05 and 0.10–0.15 m) and six weed control managements divided into two groups were analyzed: I. no soil disturbance and ground cover (no weed control, post-emergence herbicide, mechanical mower); and II. soil disturbance and no ground cover (hand-hoe weeding, rotary tiller, pre-emergence herbicide). An area of native forest was used as reference. The results showed that the volumetric water capacity derived from the SWRC can be an interesting tool to evaluate the impact of weed control managements on soil structure. Evaluations of the air-filled porosity variation for different pressure heads also presented interesting findings. Distinct results of the weed control managements were found for the different depths analyzed in relation to the forest.